The twenty-fifth international congress of the Young Linguists’ Society – XXV Congreso Internacional de la Asociación de Jóvenes Lingüistas (Valladolid 10–12 March 2010) - Michelizza, Mija (Jezikoslovni zapiski, 2015)
This article reports on the twenty-fifth international congress of the YoungLinguists’ Society held in Valladolid, Spain. It took place from 10 to 12 March 2010 and the participants included approximately 150 young scholars from various countries and continents. In addition to young linguists that presented their research in all areas of linguistics, there were invited talks by three established linguists: Teun A. van Dijk, Manuel García Teijeiro, and José Antonio Pascual.